Visual and cognitive processing of thin-ideal Instagram images containing idealized or disclaimer comments. (June 2020) - Couture Bue, Amelia C.; Harrison, Kristen
Highlights: Post-test body anxiety did not significantly differ across conditions. Comment type did not affect perceived societal pressure for thinness. Attention to comment differed across conditions, attention to model did not. Findings suggest the disclaimer was somewhat effective in preventing body anxiety. Abstract: Recent studies have demonstrated that exposure to thin-ideal social media content is associated with decreased body satisfaction, and disclaimer comments have been a proposed intervention. This experiment uses eye-tracking methods to explore the effect of disclaimer comments on participants' processing of thin-ideal Instagram images. Women ages 18–35 ( N = 181) were randomly assigned to view thin-ideal Instagram images paired with one of two caption types: traditional comments that idealized the images, or disclaimer comments that critiqued the images as unrealistic. Participants' eye movements were tracked during viewing. Following exposure, participants reported their anxiety about specific body regions, as well as their perceptions of social pressure for thinness. Post-test body anxiety and perceived pressure for thinness did not differ based on experimental condition. Results indicated some differences in message processing, with similar visual attention to the model across conditions but greater attention to the comment in the disclaimer condition. Attention to the model's thighs was associated with increased body anxiety about the thighs in both conditions, whereas attention to the model's waist was associated with increased body anxiety about the waist only in the Idealized Comment condition. This indicates that the disclaimer comments were somewhat, but not entirely, effective.